Coupling mechanical rotation and EHD actuation in flow past a cylinder - Gronskis, Alejandro (2008)
The introduction of an electro-hydrodynamic (EHD) force in high performance numerical simulation may pose some problems as a consequence of the large differences between time or spatial scales of the physics of the discharge and those of interest for the fluid flow description. In this paper, we try to simplify this problem by looking for a correspondence between the global flow modifications produced by an EHD actuation and those by a moving body surface. Direct numerical simulations (DNS) of flow past a rotating cylinder are performed. For a flow regime corresponding to Reynolds number based on the cylinder diameter and free-stream velocity of the flow of 125 (wake-transition regime), the simulations allow us to make a comparison with particle image velocimetry (PIV) measures of the flow induced by a dielectric barrier discharge (DBD) plasma actuator suitably disposed on the cylinder surface. The results obtained from the projection of mean velocity fields show that the time-averaged vortical structures in the two cases enable us to establish a good analogy between actuations produced by both mechanisms.